PENGARUH KETIDAKPASTIAN LINGKUNGAN, DESENTRALISASI, DAN SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL - Djoko Kristianto, Canggih Nur Prihatningtyas, Rispantyo & (Universitas Slamet Riyadi, 2018)
Company, profit growthThe purpose of this study to analyze: 1) the significance of the effect of environmental uncertainty on managerial performance. 2) significance of the effect of decentralization on managerial performance and 3) to analyze the significance of the effect of management accounting system on managerial performance. This research is a survey on employee of PDAM Kota Surakarta which has authority with amount of 47 employees and the whole is used as research sample.. Data collection techniques used questionnaires and literature study. Data analysis techniques use multiple linear regression, t test, F test and coefficient of determination. The result of the research shows that environmental uncertainty has positive and significant effeect to the managerial performance of PDAM Kota Surakarta. Decentralization has a positive and significant effect on the managerial performance of PDAM Kota Surakarta. Management accounting system has a positive and significant effect on the managerial performance of PDAM Kota Surakarta.Keywords: environmental uncertainty, decentralization, management accounting system, managerial performance